Uji Variasi Kadar Air (Moisture Content) Sampah Residu Terhadap Performansi Insinerator - Sua Geralta Ginting, Rio; Suprapta Winaya, I Nyoman; Agus Suryawan, I Gede Putu (Teknik Desain Mekanika; Vol 10 No 2 (2021): April 2021 : Teknik Desain Mekanika, 2021)
Abstract Water content is a component that usually carried away in waste. The effect of this water content is a decrease on caloric value of waste fuel which is affect the incinerator efficiency. High water content will decrease caloric value of waste and inhibit the combustion. This research aim is to determine the waste moisture content effect of incinerator performance, based on combustion rate, and combustion thermal capacity. With the experimental study method, the set of waste moisture content variation to be examined was determined to find its effect on the incinerator performance, that is: moisture content of 1 day drying waste, moisture content of 2 days drying waste, moisture content of 3 days drying waste, and moisture content of undried waste. The results of experimental studies showed that: 1) The highest rate of combustion system occurs in 3 days of dry waste incineration, namely 189.375 gr/minute; 2) The highest combustion thermal capacity occurred in the incineration of waste that was dried for 3 days, namely 457.204 MJ/h; Keywords: Incinerator, Residual Waste, Waste Moisture Content Variation, Performance